A novel tool for naturalistic assessment of behavioural dysregulation after traumatic brain injury: A pilot study. (6th December 2017) - McKeon, Ashlee; Terhorst, Lauren; Skidmore, Elizabeth; Ding, Dan; Cooper, Rory; McCue, Michael
ABSTRACT: Objective : This study aimed to develop a novel tool for measuring behavioural dysregulation in adults with traumatic brain injury (TBI) using objective data sources and real-world application and provide preliminary evidence for its psychometric properties. Research Design : Fourteen adults with TBI receiving services at a local brain injury rehabilitation programme completed multiple assessments of behaviour and followed by a series of challenging problem-solving tasks while being video recorded. Trained clinicians completed post-hoc behavioural assessments using the behavioural dysregulation ratings scale, and behavioural event data were then extracted for comparison with self-report measures. Results : Subject matter experts in neurorehabilitation were in 100% agreement that preliminarily, the new tool measured the construct of behavioural dysregulation. Construct validity was established through strong convergence with 'like' measures and weak correlation with 'unlike' measures. Substantial inter-rater reliability was established between two trained clinician raters. Conclusions : This study provides preliminary evidence supporting the use of a new precision measurement tool of behaviour in post-acute TBI that has the capability to be deployed naturalistically where deficits truly manifest. Future large-scaled confirmatory psychometric trials are warranted to further establish the utility of this new tool in rehabilitation research.